Comparison of the effect of mint extract and chamomile drops on the gastric residual volume of traumatic patients under mechanical ventilation and nasogastric tube feeding in the intensive care unit: A triple -blind, randomized, crossover trial - Abbasali Ebrahimian; Samaneh Rahbar; Setareh Homami; Fatemeh Paknazar; Ali Fakhr-Movahedi (Mashhad University of Medical Sciences, 2023)
Objective: Mint and chamomile can effectively reduce the gastric residual volume (GRV). This study aimed to determine the effect of mint extract and chamomile drops on the GRV of trauma patients under mechanical ventilation and nasogastric tube feeding in the intensive care unit.Materials and Methods: This study was a triple-blinded randomized clinical trial with a 2×2 crossover design. Eighty patients were randomly divided to receive mint extract and chamomile drops. Five drops of mint extract and 11 drops of chamomile were gavaged every 6 hr. GRV was measured using a syringe-aspiration method before and 3 hr after each intervention. After a 24-hour washout period, the two groups changed places.Results: In the first phase of the study, before the interventions, the GRV in the mint and chamomile groups was 14.60±7.89 and 13.79±7.12 ml, and after the interventions were 8.13±6.31 and 6.61±4.68 ml, respectively. In the study's second phase, before the interventions, the GRV in the mint and chamomile groups was 10.03±4.93 and 11.46±7.17 ml and after the interventions, GRV was 4.97±4.05 and 6.98±4.60 ml, respectively. The difference in the GRV before and after the intervention was not significantly different between the two groups. Both herbal drugs effectively reduced the GRV (p=0.382).Conclusion: Mint extract and chamomile drops are similarly effective in reducing the GRV in trauma patients under mechanical ventilation and nasogastric tube (NGT) feeding in the intensive care unit.